New species of Tenuipalpus (Acari: Tenuipalpidae) from Semidecidual Forest remnants in the State of São Paulo, Brazil - de Castro, Elizeu B.; Feres, Reinaldo J.f. (Zootaxa, 2013)
Three new species of the genus Tenuipalpus (Acariformes: Tenuipalpidae), T. tapiae sp. nov., T. apichai sp. nov., and T. nambii sp. nov. collected in Semidecidual Forest native plants in the northwest of the state of São Paulo, Brazil are described and illustrated. A key of the Brazilian species of Tenuipalpus based on females is presented.